HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA MENGGANTUNG PADA SISWA PUTRA KELAS II JURUSAN KOMPUTER JARINGAN SMK TARUNA PERSADA DUMAI TAHUN 2014-2015 - Wijayanti, Ni Putu Nita Wijayanti Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: this study was conducted to determine whether there is a relationship of explosive leg muscle power with the results of the long jump style hanging on male students majoring in computer networking class II smk cadets persada dumai years 2014-2015, so that by the time doing the long jump and leap prefix can perform well and true. The shape of this research is a correlation study, the population in this study is the son of class II student majoring in computer networks persada dumai smk cadets. The sample in this study is the son of class II student majoring in computer networks persada dumai smk cadets and amounted to 15 people. Sampling tech